2021
DOI: 10.1371/journal.pone.0255827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internal limiting membrane peeling on postoperative visual acuity in macula-off rhegmatogenous retinal detachment

Abstract: Purpose To investigate the effects of internal limiting membrane (ILM) peeling on visual acuity (VA) after rhegmatogenous retinal detachment (RRD) surgery. Methods This retrospective analysis examined the medical records of patients with RRD who underwent vitrectomy at 26 institutions. To detect prognostic factors of VA at 6 months postoperatively (post-VA), multivariate linear regression was performed with post-VA as the objective variable; ILM peeling, sex, age, preoperative VA (pre-VA), intraocular pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
2
11
0
1
Order By: Relevance
“…Our findings are consistent with ERM formation rates in the recent literature [4,[6][7][8]. The formation of ERMs that are severe enough to warrant surgical intervention also vary in the literature, with rates as low as 1.6% up to 35% of eyes after PPV for primary RRD [16]. A recent meta-analysis of 586 eyes showed that an average of 16% of eyes required a second vitrectomy for ERM peeling [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings are consistent with ERM formation rates in the recent literature [4,[6][7][8]. The formation of ERMs that are severe enough to warrant surgical intervention also vary in the literature, with rates as low as 1.6% up to 35% of eyes after PPV for primary RRD [16]. A recent meta-analysis of 586 eyes showed that an average of 16% of eyes required a second vitrectomy for ERM peeling [10].…”
Section: Discussionsupporting
confidence: 89%
“…The rate of re-operation was lower in our cohort, possibly due to advancements in surgical tools and techniques (including smaller gauge vitrectomy (25-gauge vs 20-gauge) and less use of cryotherapy). This decreased reoperation rate is despite a longer follow-up in our cohort (30 months vs 6-16 months) [3,[16][17][18][19]. This re-enforces that visually significant ERM formation is most likely to occur early in the post-operative course.…”
Section: Discussionsupporting
confidence: 56%
“…Moore et al designed an Android application to detect the pulse signal through finger contact with the camera of a mobile phone and calculate the heart rate parameters [ 6 ]. Studies have shown that a kind of ECG monitoring on mobile phone “Heart Doctor” realizes the integration of basic functions of mobile phone and ECG monitoring through three metal electrodes on the surface and internal ECG acquisition module and realizes remote ECG monitoring by cooperating with mobile communication companies [ 7 ]. A mobile healthcare multiparameter physical sign monitoring system has been applied to community health monitoring and has been successfully used to monitor the physiological health of Jiaolong divers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…En estudios comparativos para evaluar la incidencia de membranas epirretinianas después de vitrectomía con y sin retiro de la membrana limitante interna se reportan incidencias del 20% (Kumar et al 16 , n = 30), el 31% (Forlini et al 17 , n = 81) y el 46.4% (Arias et al 18 , n = 140) en los ojos que se intervinieron sin remoción quirúrgica de la membrana limitante, lo cual es consistente con los IC95% de nuestro estudio. La remoción quirúrgica de la membrana limitante interna durante la vitrectomía casi elimina la incidencia posoperatoria de membrana epirretiniana, pero puede llevar a una menor recuperación visual y a otras alteraciones funcionales clínicas o subclínicas 11,19 .…”
Section: Discussionunclassified